Analysis of the Flat Sided Volume of Elementary Mathematics Textbook Based on Praxeology - Miranda Abung; Tatang Herman (Graduate School of Universitas Negeri Malang, 2023)
Geometry is one of the materials that must be understands by students in mathematics. Even though, students still find difficulties while studying geometric, especially the concept of the volume of a cuboid. The difficulties experienced by students can be handled in various ways, one of which is by using books as a source of student learning. This study analyzed the mathematics textbooks for fifth-grade elementary school, which is the Electronic School Book (BSE). The result of this research is an analysis of the presented material on the concept of the volume of the cuboid. The volume of cuboid analyzed consisted of praxeology materials, which are types of tasks, technique, technology and theory.